The Concept of Rewards and Punishments in Religion: A Special Reference to Kitab Al-Adab of Sahih Bukhari - Zainan Nazri, Mohd Khairul Nizam; Ahmad, Mahmud; Mohamed Yusoff, Adnan; Mohd Amin, Fauzi; Mat Ishak, Mardiana; Mohd Nor, Mohd Roslan; Sidik, Mohd Akmal; Mohd Khambali Hambali, Khadijah; Suliaman, Ishak (IDOSI, 2011)
Abstract: This study examines the Prophetic tradition in Akidah or Islamic belief through the book of Sahih Bukhari which the Prophet Muhammad PBUH gave direction to educate the people by mentioning and promising the rewards (al-thawab) and punishments (al-iqab) that aiming at making the people active in persuading and what sort of rewards and punishments were mentioned that motivate the Muslims to do good deeds and stay away from negative behaviors. In fact, peace, tranquility, nobility and real greatness at home and street, in this world and the hereafter can be achieved by following his noble life and teachings. A textual and critical analysis of hadith referred to Chapter of Behavior (Kitab al-Adab) will be utilized to demonstrate the application of hadith pertaining to human behavior. The ideas presented could be further developed and appreciated by the society in related discipline in order to address contemporary challenges in understanding for future human living prospects.